Protocol for surgical and non-surgical treatment for metacarpal shaft fractures in adults: an observational feasibility study. Issue 6 (29th June 2021) - Taha, Rowa; Leighton, Paul; Bainbridge, Chris; Montgomery, Alan; Davis, Tim; Karantana, Alexia
Abstract : Introduction: Metacarpal shaft fractures (MSF) are common traumatic hand injuries that usually affect young people of working age. They place a significant burden on healthcare resources and society; however, there is a lack of evidence to guide their treatment. Identifying the most beneficial and cost-efficient treatment will ensure optimisation of care and provide economic value for the National Health Service. The aim of this study is to assess the feasibility of a randomised controlled trial comparing surgical and non-surgical treatment for MSF in adults. Methods and analysis: This is a multicentre prospective cohort study, with a nested qualitative study consisting of patient interviews and focus groups, and an embedded factorial randomised substudy evaluating the use of text messages to maximise data collection and participant retention. The outcomes of interest include eligibility, recruitment and retention rates, completion of follow-up, evaluation of primary outcome measures, calculation of the minimal clinically important difference (MCID) for selected outcome measures and establishing the feasibility of data collection methods and appropriate time-points for use in a future trial. Data will be captured using a secure online data management system. Data analyses will be descriptive and a thematic inductive analysis will be used for qualitative data. Minimum clinically important effects for each patient-reported outcome measure will be estimated using anchor-based responsiveness statistics and distribution-based methods. Ethics and dissemination: This study has received ethical approval from the Research Ethics Committee and the Health Research Authority (REC reference 20/EE/0124). Results will be made available to patients, clinicians, researchers and the funder via peer-reviewed publications and conference presentations. Social media platforms, local media and feedback from the Patient Advisory Group will be used to maximise circulation of findings to patients and the public. Trial registration number: ISRCTN13922779 .